The Government Spending Multiplier at the Zero Lower Bound: International Evidence from Historical Data - Mathias Klein; Roland Winkler (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Based on a large historical panel dataset, this paper provides robust evidence that the government spending multiplier is significantly higher when interest rates are at, or near, the zero lower bound. We estimate fiscal multipliers that are around 1.5 during zero lower bound episodes and significantly below unity outside of it. We show that the difference in multipliers is not driven by multipliers being higher during periods of economic slack.
Keywords: E32; E62; E65; 330; Government spending multiplier; zero lower bound; local projections